2018
DOI: 10.1038/s41380-018-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic loss in schizophrenia: a meta-analysis and systematic review of synaptic protein and mRNA measures

Abstract: Although synaptic loss is thought to be core to the pathophysiology of schizophrenia, the nature, consistency and magnitude of synaptic protein and mRNA changes has not been systematically appraised. Our objective was thus to systematically review and meta-analyse findings. The entire PubMed database was searched for studies from inception date to the 1st of July 2017. We selected case-control postmortem studies in schizophrenia quantifying synaptic protein or mRNA levels in brain tissue. The difference in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
138
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(165 citation statements)
references
References 150 publications
16
138
0
2
Order By: Relevance
“…Neuroimaging and post-mortem studies of individuals with SCZ or BD show reduced brain volume and spine density, particularly in the prefrontal and anterior cingulate cortex and hippocampus relative to healthy controls [1][2][3][4] . These changes coincide with reduced protein and/or mRNA levels of various synaptic markers [5][6][7][8][9][10][11] . Whereas the majority of these data were derived from post-mortem human material, the recent development of the UCB-J PET tracers, which specifically interact with the presynaptic Synaptic Vesicle glycoprotein 2A (SV2A), has enabled visualisation of pre-synaptic terminal density in the living human brain [12][13][14] .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Neuroimaging and post-mortem studies of individuals with SCZ or BD show reduced brain volume and spine density, particularly in the prefrontal and anterior cingulate cortex and hippocampus relative to healthy controls [1][2][3][4] . These changes coincide with reduced protein and/or mRNA levels of various synaptic markers [5][6][7][8][9][10][11] . Whereas the majority of these data were derived from post-mortem human material, the recent development of the UCB-J PET tracers, which specifically interact with the presynaptic Synaptic Vesicle glycoprotein 2A (SV2A), has enabled visualisation of pre-synaptic terminal density in the living human brain [12][13][14] .…”
Section: Introductionmentioning
confidence: 92%
“…Our data presented here provide evidence that APDs are unlikely to account for the reduced SV2A binding in SCZ patients as observed by PET 19 . More broadly, the lack of change in either SV2A, NLGN or synaptic (overlapping SV2A/NLGN) cluster density suggests APD treatment may be unrelated to changes in other synaptic markers found in human post mortem SCZ tissue, such as reduced SYN levels 8,64 . Whether SV2A protein levels are reduced in BD and SCZ post-mortem brain tissue has yet to be investigated, but could be expected to reflect the same changes as those observed with SYN.…”
Section: Implications For Human Studiesmentioning
confidence: 99%
“…Additional evidence for the DMN and remission has been reported by Manoliou and colleagues . Loss of key synaptic proteins that are essential for spine formation and plasticity in cortical and hippocampal areas, including the subthalamic nucleus, is likely to be critical for the pathophysiology of schizophrenia and response to APD treatment …”
Section: Discussionmentioning
confidence: 73%
“…31 Loss of key synaptic proteins that are essential for spine formation and plasticity in cortical and hippocampal areas, including the subthalamic nucleus, is likely to be critical for the pathophysiology of schizophrenia and response to APD treatment. 15,32 There was nothing remarkable about the baseline brain MRI in this patient, including total gray matter compared with other patients in the study, or specific regional shapes or sizes, to suggest some comparable improvement in gray matter as the basis for the remission of the bipolar and psychotic depressive periods previously noted. Conceivably, gray matter renewal in other regions of the brain may have been responsible for the termination of those periods.…”
Section: Improvement In Gray Mattermentioning
confidence: 71%
“…From an oligodendrocyte-based context, we observed that multiple forms of synapse function and regulation were enriched -specifically, the regulation of trans-synaptic signaling (p<1.95e-8) [45], modulation of chemical synaptic transmission (p<1.80e-8) [46], and neuron-to-neuron synapses (p<2.57e-11) [47]. The overarching theme of these observations concerns furthered impacts on signaling and transmission between neurons which Schizophrenia pathology widely believes to be implicated [45,46,48,49]. This is in line with the physical effects of SCZ, both positive and negative, as overactive dopamine channels have been suggested to create hallucinations (visual and auditory) [50], which is a hallmark feature of SCZ diagnoses.…”
Section: Excitatory Microgliamentioning
confidence: 92%